ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI EFEKTIVITAS PELATIHAN PERIKANAN BUDIDAYA: STUDI KASUS DI WILAYAH KERJA BALAI DIKLAT PERIKANAN BANYUWANGI - Madyunin Madyunin (UNIVERSITAS PGRI MADIUN, 2016)
One of the solutions to pursue lack of the aquaculture technology is to provide a training program for fish farmer.This research was used using the analysis of factors affecting the training effectiveness. Objective of the research were to measure the causality relations of the training equipment factor, the quality of the participants and the material, the provision of the training methods, and the quality of the trainers toward the effectiveness of training program. Object ofthe research was the Purnawidya of aquaculture training in the Banyuwangi Training Center which spread out in 3 provinces with over 105 participated. Data were analyzed by using the Structural Equation Modeling (SEM). Results shows that equipments have a positive significant impact toward the effectiveness of the training and the efficiency of the aquaculture performance. The quality of the training and the material, the methods, and the quality of the trainers notsignificant impacted the of effectiveness of the training program. The result recommends that the Banyuwangi Training Center need to improve the criteria for selecting the participants, the quality of the materials, and to improve the quality of the trainers.